Phase formation, morphology and magnetic properties of MgFe2O4 nanoparticles synthesized by hydrothermal technique - Nonkumwong,J. (Elsevier, 2015)
© 2015 Elsevier B.V. All rights reserved. In the present work, the processing conditions for obtaining monodispersed magnesium ferrite (MgFe2O4) nanoparticles with the desired morphology and relatively high saturation magnetization via hydrothermal technique were developed. For the first time, the effects of base type and reaction conditions (i.e. temperature and time) on phase formation, morphology and magnetic properties of the obtained products were determined by using a combination of XRD, TEM/EDX and VSM techniques. It is seen that the saturation magnetization of the particles can be increased by employing lower reaction temperature and/or shorter reaction time, while narrow size distribution of the particles can be maintained. In addition, it was found that pure phase of superparamagnetic MgFe2O4 nanoparticles with the smallest size of about 65 nm was obtained by using CH3COONa as a base at 180 °C for 14 h.